Discrete-time parametric amplification based on a three-terminal MOS varactor analysis and experimental results. - Ranganathan, S.
This paper discusses discrete-time parametric amplification based on large-signal operation of a three-terminal MOS varactor. The principle of operation is described in detail and analytical estimates of performance are derived. Detailed measurements are reported for a prototype implemented in standard digital CMOS technology. It is demonstrated that the technique can be used to provide micropower, low-gain, low-noise, large-signal amplification.
Keywords: Analytical estimates; Discrete-time parametric amplification; Large-signal amplification; Large-signal operation; Low-gain.; Low-noise.; Micropower; Parametric amplifier; Prototype implementation; Standard digital CMOS technology; Three-terminal MOS varactor